2007
DOI: 10.1002/mds.21401
|View full text |Cite
|
Sign up to set email alerts
|

Cabergoline compared to levodopa in the treatment of patients with severe restless legs syndrome: Results from a multi‐center, randomized, active controlled trial

Abstract: We report the first large-scale double-blind, randomly assigned study to compare two active dopaminergic therapies for Restless Legs Syndrome (RLS), the dopamine agonist cabergoline (CAB) and levodopa/benserazide (levodopa). Patients with idiopathic RLS were treated with fixed daily doses of 2 or 3 mg CAB or 200 or 300 mg levodopa for 30 weeks. Efficacy was assessed by changes in the IRLS (International RLS Severity Scale) and by time to discontinuation of treatment due to loss of efficacy or augmentation. 361… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 28 publications
1
65
0
3
Order By: Relevance
“…No total score is defined but the scales are analyzed separately to establish a profile of changes over time and are useful both on weekly and daily (diaries) basis. The RLS-6 scales have been validated in a large trial (n ϭ 361, 15 ) and the evaluation shows moderate correlation between the RLS-6 scales and the IRLS. Sensitivity for placebo effects seems to be lower than for the IRLS or the CGI.…”
Section: S486mentioning
confidence: 99%
See 1 more Smart Citation
“…No total score is defined but the scales are analyzed separately to establish a profile of changes over time and are useful both on weekly and daily (diaries) basis. The RLS-6 scales have been validated in a large trial (n ϭ 361, 15 ) and the evaluation shows moderate correlation between the RLS-6 scales and the IRLS. Sensitivity for placebo effects seems to be lower than for the IRLS or the CGI.…”
Section: S486mentioning
confidence: 99%
“…Psychometric indicators were good to excellent in this study as well in a reanalysis with the data of a large scale clinical trial population. 15 The authors recommend analysis of the profile of the individual items in addition to the total score. The QoL-RLS was applied in several clinical trials; in all these trials, the total score was more improved by active dopamine agonist therapy than by placebo (e.g., Refs.…”
Section: S488 R Kohnen Et Almentioning
confidence: 99%
“…Therefore, placebo-controlled studies should be restricted to 12 weeks, including at least 4 weeks of maintenance treatment. More active comparator trials using dopaminergic 55 or nondopaminergic comparators like opioids should be conducted in the future.…”
Section: Therapeutic Confirmatory Studies Active Comparator Trialsmentioning
confidence: 99%
“…Several randomized controlled studies showed significant changes if patients were treated with 0.25-6 mg/day of ropinirole for 4-12 weeks (table 4) [38,39,40]. The efficacy of ergot agonists such as cabergoline (2 mg) was demonstrated in studies employing levodopa as the active comparator [41]. Treatment with 0.125-0.75 mg/day of pramipexole was also explored, with positive results [42,43].…”
Section: The Place Of Rotigotine In the Treatment Of Rlsmentioning
confidence: 99%